K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 5 2020

Pt<=> 3-50x+4x^2=4x^2+x-40<=>51x=43<=>x=43/51

18 tháng 3 2020

\(\frac{3}{2x+5}-\frac{40}{4x^2-25}+\frac{1}{2x-5}\)

\(=\frac{3\cdot\left(2x-5\right)}{4x^2-25}-\frac{40}{4x^2-25}+\frac{2x+5}{4x^2-25}\)

\(=\frac{6x-15-40+2x+5}{\left(2x+5\right)\cdot\left(2x-5\right)}=\frac{8x-50}{\left(2x+5\right)\cdot\left(2x-5\right)}\)

24 tháng 10 2017

mk ko bt 123

18 tháng 11 2019

Suy ra (2x-4)-(3x-3×5)=1 Suy ra(2x-4)-3x+15=1 Suy ra 2x-4-3x+15=1 Suy ra (2x-3x)+(15-4)=1 -1x+11=1 1-11=-1x -1x=-10 X=10

30 tháng 9 2020

Bài 1.

1) ( 2x + 1 )3 - ( 2x + 1 )( 4x2 - 2x + 1 ) - 3( 2x - 1 ) = 15

<=> 8x3 + 12x2 + 6x + 1 - [ ( 2x )3 - 13 ] - 6x + 3 = 15

<=> 8x3 + 12x2 + 4 - 8x3 + 1 = 15

<=> 12x2 + 15 = 15

<=> 12x2 = 0

<=> x = 0

2) x( x - 4 )( x + 4 ) - ( x - 5 )( x2 + 5x + 25 ) = 13

<=> x( x2 - 16 ) - ( x3 - 53 ) = 13

<=> x3 - 16x - x3 + 125 = 13

<=> 125 - 16x = 13

<=> 16x = 112

<=> x = 7

Bài 2.

A = ( x + 5 )( x2 - 5x + 25 ) - ( 2x + 1 )3 - 28x3 + 3x( -11x + 5 )

= x3 + 53 - ( 8x3 + 12x2 + 6x + 1 ) - 28x3 - 33x2 + 15x

= -27x3 + 125 - 8x3 - 12x2 - 6x - 1 - 33x2 + 15x

= -33x3 - 45x2 + 9x + 124 ( có phụ thuộc vào biến )

B = ( 3x + 2 )3 - 18x( 3x + 2 ) + ( x - 1 )3 - 28x+ 3x( x - 1 )

= 27x3 + 54x2 + 36x + 8 - 54x2 - 36x + x3 - 3x2 + 3x - 1 - 28x3 + 3x2 - 3x

= 7 ( đpcm )

C = ( 4x - 1 )( 16x2 + 4x + 1 ) - ( 4x + 1 )3 + 12( 4x + 1 )3 + 12( 4x + 1 ) - 15

= ( 4x )3 - 13 - [ ( 4x + 1 )3 - 12( 4x + 1 )3 - 12( 4x + 1 ) ] - 15

= 64x3 - 1 - ( 4x + 1 )[ ( 4x + 1 )2 - 12( 4x + 1 )2 - 12 ] - 15

= 64x3 - 16 - ( 4x + 1 )[ 16x2 + 8x + 1 - 12( 16x2 + 8x + 1 ) - 12 ]

= 64x3 - 16 - ( 4x + 1 )( 16x2 + 8x - 11 - 192x2 - 96x - 12 )

= 64x3 - 16 - ( 4x + 1 )( -176x2 - 88x - 23 )

= 64x3 - 16 - ( -704x3 - 528x2 - 180x - 23 )

= 64x3 - 16 + 704x3 + 528x2 + 180x + 23 

= 768x3 + 528x2 + 180x + 7 ( có phụ thuộc vào biến )

18 tháng 1 2022

\(\text{2x - (x - 3)(5 - x) = (x+4)}^2.\)

\(\Leftrightarrow2x-\left(5x-x^2-15+3x\right)=x^2+8x+16.\)

\(\Leftrightarrow2x-5x+x^2+15-3x-x^2-8x-16=0.\)

\(\Leftrightarrow-14x-1=0.\Leftrightarrow x=\dfrac{-1}{14}.\)

\(\text{(4x + 1)(x - 2) + 25 = (2x+3)}^2-4x.\)

\(\Leftrightarrow4x^2-8x+x-2+25=4x^2+12x+9-4x.\)

\(\Leftrightarrow-15x+14=0.\Leftrightarrow x=\dfrac{14}{15}.\)

28 tháng 10 2020

( 2x + 1 )3 - ( 3x + 2 )2 = ( 2x - 5 )( 4x2 + 10x + 25 ) + 6x( 2x + 1 ) - 9x2

⇔ 8x3 + 12x2 + 6x + 1 - ( 9x2 + 12x + 4 ) = 8x3 - 125 + 12x2 + 6x - 9x2

⇔ 8x3 + 12x2 + 6x + 1 - 9x2 - 12x - 4 = 8x3 + 3x2 + 6x - 125

⇔ 8x3 + 3x2 - 6x - 3 = 8x3 + 3x2 + 6x - 125

⇔ 8x3 + 3x2 - 6x - 3 - 8x3 - 3x2 - 6x + 125 = 0

⇔ -12x + 122 = 0

⇔ -12x = -122

⇔ x = 61/6

12 tháng 6 2018

+)   (5x-1). (2x+3)-3. (3x-1)=0

10x^2+15x-2x-3 - 9x+3=0

10x^2 +8x=0

2x(5x+4)=0

=> x=0 hoặc x= -4/5

+)    x^3 (2x-3)-x^2 (4x^2-6x+2)=0

2x^4 -3x^3 -4x^4 + 6x^3 - 2x^2=0

-2x^4 + 3x^3-2x^2=0

x^2(-2x^2+x-2)=0

-2x^2(x-1)^2=0

=> x=0 hoặc x=1

+)   x (x-1)-x^2+2x=5

x^2 -x -x^2+2x=5

x=5

+)     8 (x-2)-2 (3x-4)=25

8x - 16-6x+8=25

2x=33

x=33/2

5 tháng 8 2016

1) \(\left(x+1\right)\left(x^2-2x+1\right)=\left(x+1\right)\left(x-1\right)^2\)

2) \(\left(2x+5\right)\left(4x^2-10x+25\right)=\left(2x\right)^3+5^3=8x^3+125\)

4) \(\left(\frac{1}{2}-x\right)\left(\frac{1}{4}+\frac{1}{2}x+x^2\right)=\left(\frac{1}{2}\right)^3-x^3=\frac{1}{8}-x^3\)

5) \(\left(2x-3y\right)\left(4x^2+6xy+9y^2\right)=\left(2x\right)^3-\left(3y\right)^3=8x^3-27y^3\)

6) \(\left(2x+5\right)\left(4x^2-10x+25\right)=\left(2x\right)^3+5^3=8x^3+125\)

3) Đề thiếu

5 tháng 8 2016

\(1,\left(x+1\right)\left(x^2-2x+1\right)=\left(x+1\right)\left(x-1\right)^2\)
\(2,\left(2x+5\right)\left(4x^2-10x+25\right)=\left(2x\right)^3+5^3=8x^3+125\)
\(3,\left(x+2\right)^2=x^2+2.x.2+2^2=x^2+4x+2\)
\(4,\left(\frac{1}{2}-x\right)\left(\frac{1}{4}+\frac{1}{2}x+x^2\right)=\left(\frac{1}{2}\right)^3-x^3=\frac{1}{8}-x^3\)
\(5,\left(2x-3y\right)\left(4x^2+6xy+9y^2\right)=\left(2x\right)^3-\left(3y\right)^3=8x^3-27y^3\)
\(6,\left(2x+5\right)\left(4x^2-10x+25\right)=\left(2x\right)^3+5^3=8x^3+125\)